Possibilities of using simulated virtual reality technique for learning product base design: case study on industry related courses in art & design department - Azizan, Hasnul Azwan; Ismail, Abdullah Kula; Naser, Faradiba Liana (2011)
The massive wave of technological advancement that can be expected was Virtual Reality. The mass use of computers in the current century had let a wide array of useful usage in the society. In the product development for example, the usage of advance computers and machinery has led to mass amount of product design oriented based on this kind of technology. This research is an extension of the phenomenon, which the technology has taken its tool on the local industry with the linkages between academic understanding in coping up with persisting trends and the job market. One of the aspect of virtual reality on the industry is the advance manufacturing and cost reduction time persuading the older methods of production and manufacturing, with the initial technology have its abundant cost, the question is can local product development industry adopt virtual reality technology as well as other overseas counterparts. The Investigation on localized company have proven a certain revealing of problems regarding cost and adaptability of the technology, of course technology are always welcomed at our doorstep, but how far can it go in terms of helping out the struggling local businesses and the people who depend on it. The related problems revealed in this research is encountered in the design education or to be specified classes which have a tie in projects base on computer aided design targeted to give the design student an advantage in the outside world. The mutual understanding and needs of the group is examine with general understanding of the emerging virtual technology and design culture with the essential awareness on thriving the next wave of future trends.